Integrating crystallisation into transmembrane chemical absorption: Process intensification for ammonia separation from anaerobic digestate - Davey, Christopher J.; Hermassi, Mehrez; Allard, E.; Amine, M.; Sweet, N.; Schmieder Gaite, T.; McLeod, A.; McAdam, Ewan J. (Elsevier, 2020)
In this study, reactive crystallisation is introduced into a liquid-liquid membrane contactor for the selective separation, purification and recovery of ammonia from concentrated waste. Whilst liquid-liquid membrane contactor technology has been previously demonstrated for ammonia absorption, further process intensification can be achieved by incorporating crystallisation into transmembrane chemisorption to recover the ammonia as crystalline ammonium sulphate. Reactive crystallisation occurred in the draw solution (sulphuric acid) which was supplied to the lumen-side of the polypropylene hollow-fibre. The ammonium sulphate concentration in the draw solution increased through ammonia mass transfer to supersaturation, at which time induction (the onset of nucleation) commenced. Ammonia mass transfer at draw concentrations above the solubility limit was not limited provided sufficient ‘free’ sulphate was available. This resulted in nucleation which occurred at a low level of supersaturation (C/C*, 1.03) to produce small crystals of around 2.5 μm, which indicated that nucleation was favoured. The nucleation rate was found to be proportional to the ammonia flux in the draw solution. As the solution became more saturated, crystal number increased but crystal growth was comparatively small; this is symptomatic of reactive crystallisation, where the rate of reaction exceeds the rate of mass transfer. Due to the large difference in the ratio between the lumen internal diameter and the mean crystal diameter (dfibre/dmean,CSD, ∼180), no fibre clogging was observed despite facilitating crystallisation on the lumen-side of the membrane. Transmembrane chemisorption crystallisation presents a feasible process intensification for the selective separation of ammonia from environmental applications. For its integration into environmental applications, solutions to wetting and fouling remain due to associative interactions with the complex organic matrix that are practically achievable through engineering intervention. Subsequent transformation of ammonia into a crystalline phase of ammonium sulphate presents a new product which is of commercial interest.
Keywords: Membrane contactor; Nitrogen; Perstraction; Hydrophobic; Microporous; Lumen-side crystallisation